2013
DOI: 10.1016/j.bbamem.2013.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene nanoparticle exposure induces ion-selective pores in lipid bilayers

Abstract: A diverse range of molecular interactions can occur between engineered nanomaterials (ENM) and biomembranes, some of which could lead to toxic outcomes following human exposure to ENM. In this study, we adapted electrophysiology methods to investigate the ability of 20 nm polystyrene nanoparticles (PNP) to induce pores in model bilayer lipid membranes (BLM) that mimic biomembranes. PNP charge was varied using PNP decorated with either positive (amidine) groups or negative (carboxyl) groups, and BLM charge was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
5
15
0
Order By: Relevance
“…In the in vitro cellular uptake studies, both Prussian blue staining and ICP-MS measurement demonstrated that PEI-coated IONPs were internalized more efficiently than PEGylated IONPs with the same particle size, which may be due to the affinity of cationic nanoparticles to the negative phospholipid head groups or protein domains on cellular membranes 20 . Besides, small PEGylated IONPs (10 nm) showed relatively higher cellular uptake than large ones (30 nm), which is consistent with other previously reported nanoparticles 7 .…”
Section: Discussionmentioning
confidence: 97%
“…In the in vitro cellular uptake studies, both Prussian blue staining and ICP-MS measurement demonstrated that PEI-coated IONPs were internalized more efficiently than PEGylated IONPs with the same particle size, which may be due to the affinity of cationic nanoparticles to the negative phospholipid head groups or protein domains on cellular membranes 20 . Besides, small PEGylated IONPs (10 nm) showed relatively higher cellular uptake than large ones (30 nm), which is consistent with other previously reported nanoparticles 7 .…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the results reported in Table 2 and Table S3 NPs. 56 We speculate that a SLB (as in our case) is more resistant to external stimulus and no pores are formed. Anionic PS NPs of the same size but different surface charge density were found to adsorb on DOPC LUVs (large unilamellar vesicles) inducing a local fluid to gel transition of the lipids with consequent shrinking of the membrane, decrease of the APM and loss of hydration due to NP binding.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 For example, electrical measurements of ENM-exposed suspended bilayers have shown that quantum dots, carbon nanotubes and polystyrene or silica nanospheres render bilayers permeable to ions, indicating a nanoparticle-induced perturbation of the bilayer structure. [31][32][33][34][35] It has also been visualized with atomic force microscopy that cationic dendrimers and silica nanospheres can create holes in mica-supported bilayers, 36 and fluorimetry measurements have demonstrated that titanium dioxide and silica nanospheres, cationic and anionic gold nanoparticles and protein-coated carbon nanotubes are all able to induce the release of fluorescent dyes from lipid vesicles. [37][38][39][40] But because most studies only concern a small number of ENM species, structure-function relationships remain elusive.…”
Section: Introductionmentioning
confidence: 99%